2022
DOI: 10.1039/d1na00753j
|View full text |Cite
|
Sign up to set email alerts
|

Loading of DOX into a tetrahedral DNA nanostructure: the corner does matter

Abstract: With the rapid development of nanotechnology, various DNA nanostructures have been synthesized and widely used in the drug delivery. However, the underlying mechanisms of drug molecules loading into the DNA...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…4 A). Since then, DOX has become the most popular model drug in drug delivery, with nucleic acid as a carrier 72 , 73 , 74 .
Figure 4 Examples of ApDC from physical conjugation.
…”
Section: Small Molecule Drug-based Apdcmentioning
confidence: 99%
“…4 A). Since then, DOX has become the most popular model drug in drug delivery, with nucleic acid as a carrier 72 , 73 , 74 .
Figure 4 Examples of ApDC from physical conjugation.
…”
Section: Small Molecule Drug-based Apdcmentioning
confidence: 99%
“…This can be achieved using different non-covalent binding modes, including intercalation, [12][13][14] groove-binding, [15][16][17] or simple electrostatic binding. [18][19][20] Depending on the drug molecule in question, these rather straightforward drug loading approaches unfortunately often suffer from complications such as a competition of several different binding modes, 15,21,22 limited accessibility of binding sites, 15,23 and difficulties in the unambiguous detection of drug-DNA binding events. The latter is usually attempted by analyzing binding-specific UV-vis or fluorescence spectroscopic signatures, which may, however, be obscured by or sometimes even originate in other processes such as drug aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…17 These drugloaded DNA nanostructures increase the e cacy of chemotherapy, decrease the adverse side effects and show no signi cant cytotoxicity in vivo and in vitro. 18,19 The DNA tetrahedron (TDN) is one of the most promising nanoconstructs due to its straightforward and predictable assembly in a quantitative manner. 19,20 Turber eld et al previously demonstrated the successful cellular uptake of TDN into mammalian cells 21 and Jiang et al described its' use as a DOX nanocarrier for targeted delivery into drug-resistant MCF7 cells.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 The DNA tetrahedron (TDN) is one of the most promising nanoconstructs due to its straightforward and predictable assembly in a quantitative manner. 19,20 Turber eld et al previously demonstrated the successful cellular uptake of TDN into mammalian cells 21 and Jiang et al described its' use as a DOX nanocarrier for targeted delivery into drug-resistant MCF7 cells. 22 The uptake of TDN into mammalian cells is an energy-dependent endocytosis process.…”
Section: Introductionmentioning
confidence: 99%